Patterns of Transmission Dynamics of Severe Fever with Thrombocytopenia Syndrome Virus in Dalian: Roles of Systemic, Co-Feeding, and Transovarial Routes (CSIAM Transactions on Life Sciences, 2025)
Severe fever with thrombocytopenia syndrome (SFTS) is an emerging tick-borne zoonotic disease caused by severe fever with thrombocytopenia syndrome virus.In recent years, there has been an increasing number of human SFTS cases in centraland northeast China. In the study region, Dalian, the number of human cases in yearsbetween 2011 and 2019 exhibited recurrent patterns in synchrony with the seasonaltemperature variation. Here, we develop a transmission dynamics model to incorporate contact characteristics of animal and human hosts from published literature,and fit the model to historical temperature and human incidence data in our studyregion to analyze trends in human SFTS incidence and the time trends of SFTS prevalence within the natural tick-host cycle. Our analysis highlights the contributions ofthe systemic, co-feeding, and transovarial transmission routes, and provides insightsfor cost-effective public health interventions targeted to reducing transmission in thesecoexisting transmission pathways.
Keywords: SFTS; dynamics model; basic reproduction number; sensitivity analysis.